ANALISIS KEBUTUHAN PENGEMBANGAN INSTRUMEN TES KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK - Zahra, Nur Izhma Adzkia; Langlang Handayani; Wiwi Isnaeni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Problem-solving ability is an important aspect of mathematics learning, asemphasized in the mathematics learning objectives. However, currently availabletest instruments are still dominated by routine tests and cannot measure students'mathematical problem-solving abilities. This literature review aims to analyze theneed to develop a test instrument capable of measuring mathematical problemsolving abilities validly and reliably. The analysis results indicate the need for aninstrument that contains non-routine (contextual) questions, contains descriptivequestions that can measure students' understanding process in obtaining the finalanswer, and is equipped with an assessment rubric tailored to the indicators ofmathematical problem-solving abilities, namely understanding the problem,planning a solution, implementing the solution plan, and reviewing.